How policy on employee involvement in work reintegration can yield its opposite: employee experiences in a Canadian setting. (April 2013) - Maiwald, Karin; Meershoek, Agnes; de Rijk, Angelique; Nijhuis, Frans
<x xml:space="preserve">Abstract</x> Purpose: Canada has a long tradition of involving employee representatives in developing work reintegration policies and expects this to positively affect employee involvement to improve work reintegration success. The purpose of this study was to examine employee involvement in reintegration in a Canadian province as experienced by employees. Method: Fourteen semi-structured interviews were held with employees in a healthcare organization. The interview topic list was based on a review of local reintegration policy documents and literature. Interviews were transcribed verbatim and analysed using ethnographic methodology. Results Employees do not feel in control of their reintegration trajectory. In the phase of reporting sickness absence, they wrestle with a lack of understanding on how to report in sick. In the phase of reintegration planning and coordination, they hesitate to get involved in the organization of reintegration. In the phase of reintegration plan execution, employees encounter unfulfilled expectations on interventions. Conclusion: Employee involvement in the organization of reintegration makes them responsible for the development of reintegration trajectories. However, they consider themselves often incapable of completing this in practice. Moreover, employees experience that their contribution can boomerang on them.